Reforming Youth Allowance The "Independent-at-Home" Category - Chapman, B; Lounkaew, K (My University, 2010)
The Review of Australian Higher Education (2008) recommended the elimination of the Youth Allowance (YA) category known as “Independent-at-Home” (IAH), a policy position which has been endorsed by the Australian Government. The concern is students gaining access to YA through this eligibility criterion are not disadvantaged and that consequently this aspect of the system is inequitably targeted. To cast light on this possibility, the research reported here examines the household income circumstances of individuals in the IAH category in a comparison with otherwise similar students. The research methods employed are indirectly due to the lack of available data, but we are able to adjust information from the HILDA survey to address the issue. The evidence is that, in the 2001 to 2006 period, a large proportion of those in the IAH category were not disadvantaged, which is support for the position of the Review and the government’s response to it.
Economic Papers: A journal of applied economics and policy
Keywords: Families; Families -- Adolescents and Youth; Benefits and Payments -- Allowances; Benefits and Payments; Adolescents and youth; Families and relationships; Families; Benefits and Payments; Allowances; Adolescents and Youth; Adolescents and youth; Families and relationships